Fibroscan and low-density lipoprotein as determinants of severe liver fibrosis in diabetic patients with nonalcoholic fatty liver disease. Issue 12 (December 2019) - Jaafar, Rola F.; Hajj Ali, Adel M.; Zaghal, Ahmad M.; Kanso, Mariam; Habib, Salim G.; Halaoui, Adham F.; Daniel, Fady; Mokaddem, Farah; Khalife, Mohamad J.; Mukherji, Deborah M.; Faraj, Walid G.
Abstract : Background: Fibroscan is an effective and noninvasive tool to quantify fibrosis and steatosis in liver diseases including nonalcoholic fatty liver disease (NAFLD). Type-2-diabetes is a known risk factor for worse prognosis in NAFLD. In this study, we compare liver status in NAFDL diabetic and nondiabetic patients, identify potential risk factors, and determine the usefulness of Fibroscan in this population. Patients and methods: The charts of all patients with NAFLD who underwent Fibroscan at our institution were reviewed. Fibroscan results, demographics, and clinical data were collected and analyzed using SPSS software. Results: Of the 248 NAFLD patients, 73 (29.4%) were diabetic and 175 (70.6%) were nondiabetic. As detected by the NAFLD' liver stiffness measure, 35 (47.94%) diabetic patients had severe liver fibrosis (F4) in contrast to only 46 (26.3%) nondiabetics. Diabetic patients also presented more with hypertension, dyslipidemia, coronary artery disease, and chronic kidney disease. Liver steatosis, liver function tests, and noninvasive scores did not vary significantly between the two groups, except for γ-glutamyltransferase, prothrombin time-international normalized ratio, and BMI-alanine aminotransferase ratio-diabetes score. Diabetic patients had significantly lower high-density lipoproteins and low-density lipoproteins. Conclusion: Fibroscan results and low-density lipoprotein are potential diagnostic factors of liver fibrosis in diabetic patients with NAFLD. Further studies are necessary to verify liver fibrosis diagnostic tools and prognostic and genetic markers in diabetic patients.